Theory and modeling of electron fishbones. (20th October 2016) - Vlad, G; Fusco, V; Briguglio, S; Fogaccia, G; Zonca, F; Wang, X
Abstract: Internal kink instabilities exhibiting fishbone like behavior have been observed in a variety of experiments where a high energy electron population, generated by strong auxiliary heating and/or current drive systems, was present. After briefly reviewing the experimental evidences of energetic electrons driven fishbones, and the main results of linear and nonlinear theory of electron fishbones, the results of global, self-consistent, nonlinear hybrid MHD-Gyrokinetic simulations will be presented. To this purpose, the extended/hybrid MHD-Gyrokinetic code XHMGC will be used. Linear dynamics analysis will enlighten the effect of considering kinetic thermal ion compressibility and diamagnetic response, and kinetic thermal electrons compressibility, in addition to the energetic electron contribution. Nonlinear saturation and energetic electron transport will also be addressed, making extensive use of Hamiltonian mapping techniques, discussing both centrally peaked and off-axis peaked energetic electron profiles. It will be shown that centrally peaked energetic electron profiles are characterized by resonant excitation and nonlinear response of deeply trapped energetic electrons. On the other side, off-axis peaked energetic electron profiles are characterized by resonant excitation and nonlinear response of barely circulating energetic electrons which experience toroidal precession reversal of their motion.